Monitoring Pemakaian Arus Listrik Pada Alat Rumah Tangga Dengan Menggunakan Aplikasi Blynk Berbasis Internet Of Things - Hermanto; Agustini, Ajeng Ayu (MEANS (Media Informasi Analisa dan Sistem), 2022)
Currently, the monitoring system for electrical energy can only be monitored by PLN. Electricity users usually can only see the number of usage each month without knowing the electricity consumption every time. Excessive use of electrical energy will cause soaring payments. Therefore, this research was conducted to monitor the electrical power used at home via an internet connection using the blynk application. This study aims to determine the amount of electrical energy consumption every day. This lot-based monitoring tool uses the PZEM-004T sensor to read the amount of electrical energy consumption such as voltage, current, power, and energy. As for the media interface that displays the amount of electrical energy consumption using the Blynk application.